WhatsApp-Mediated Economics Learning and Student Learning Interest in Senior High School Education - A. Alyana; Muhammad Yany; Sandi (EduLine: Journal of Education and Learning Innovation, 2026)
The integration of digital communication technology in education has become an effective approach to enhance student engagement and learning interest. WhatsApp, as a widely used application, offers various features that support interaction, material delivery, and communication between teachers and students; however, its effectiveness in influencing students’ learning interest requires empirical investigation. This study aims to examine the effect of WhatsApp usage on students’ learning interest in Economics among tenth-grade students at SMA Negeri 18 Bone. The research employed a quantitative approach with an ex post facto design, involving 32 students selected through simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed through simple linear regression. The results indicate that WhatsApp usage has a positive effect on students’ learning interest (sig. 0.022 < 0.05), with a moderate relationship (R = 0.402) and a contribution of 16.2% (R² = 0.162). In conclusion, WhatsApp can be utilized as a supportive learning medium to enhance students’ learning interest, although its influence is not dominant and is affected by other factors beyond this study.